Local Communities in Batavia Resisting VOC Domination, 17th – 18th Centuries - Maulinda Rahma Sari; Silvy Mei Pradita; Adlil Dzil Jabar (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
This study examines the role of local communities in resisting the domination of the Dutch East India Company (VOC) in Batavia in the 17th and 18th centuries, focusing on three multi-ethnic villages: Kampung Melayu, Kampung Jawa, and Pekojan. The main problem of this study is the tendency of colonial historiography to emphasize large-scale resistance, thus ignoring the forms of micro-resistance that occurred in the daily lives of village communities. This study uses historical research methods that include heuristics, source criticism, interpretation, and historiography. The research sources come from edited VOC archives and authoritative scholarly works such as those by Denys Lombard, Leonard Blussé, Claudine Salmon, and M.C. Ricklefs. The results show that village communities were not passive, but rather played an active role in various forms of everyday resistance, such as small-scale smuggling, tax evasion, the formation of informal trade networks, cross-ethnic solidarity, and social and cultural resistance. These findings confirm that multi-ethnic villages had a strategic role in weakening the VOC's authority at the grassroots level and made an important contribution in shaping the social dynamics of Batavia during the colonial period.